APPLICATION OF THE VALUE OF STUDENT DATA PROCESSING PROGRAM JUNIOR HIGH SCHOOL XYZ USING VISUAL BASIC 6.0 - Supriyono Supriyono; Don Elsyafitra, Skom Don Elsyafitra, Skom (Jurnal Sistem Informasi, 2003)
Much of the information that does not irregular in the process of calculation or searchvalues and processes manually, causing the value produced makes it look longer,complicated and less accurate. When the computerized system is used, then theconstraints encountered in the process of searching old values can be overcomebecause of the stored data into the file storage media. Also expected the teachers nolonger have difficulty in making entry value.